Study On Seriousness Of Addiction And Aggressive Behaviour Influenced By Type Of Drugs And Duration Of Addiction Among Inmates In Cure And Care Rehabilitation Centre, Pahang - Suhaizak bin Ab. Wahab; Mohd Faizal bin Mat Yaacob; Rozana binti Arjo; Mohd Rizam bin Surani (2024)
Seriousness of addiction and aggressive behaviour is the key factor to predict the success of the inmates undergoing rehabilitation in the centre thus to prevent relapse after completing rehabilitation program. This study is to measure the level of seriousness of addiction and the level of aggressiveness for each study are using Drug Abuse Screening Test (DAST-20) and Aggressive Questionnaires (AQ). A total of 213 respondents from 4 drug rehabilitation centre in Peninsular Malaysia were chosen using random sampling. Data were analysing using descriptive analyses. Results demonstrated that majority of the respondents are in the moderate and severe addiction. Whereas as far as aggressive are concerned, majority of respondents are vulnerable for aggressive behavior. The result also demonstrated that seriousness of addiction are correlated with the aggressive behaviour of the inmates.